2018
DOI: 10.4236/ojog.2018.89080
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Epidural Analgesia in Labour on Neonatal and Maternal Outcomes

Abstract: Aim: To evaluate the effect of epidural analgesia during labour on neonatal-maternal outcomes. Methods: A retrospective cohort study of nulliparous parturients who gave birth in Västernorrland County, Sweden, over a 2-year period between 2015 and 2016. Neonatal outcomes (Apgar score at 5 min and umbilical cord arterial blood gases), maternal outcomes (perineal injury, total bleeding volume and maternal satisfaction with birth) and labour parameters (mode of delivery and the durations of labour and postpartum h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Majority of previous studies had similar observation. 7,17,18,[56][57][58] Hintz et al 59 and Tawhid Soderholm et al 15 found a decrease in cord arterial pH <7.1 in association with EA. One study 19 observed better cord pH in patients with EA.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Majority of previous studies had similar observation. 7,17,18,[56][57][58] Hintz et al 59 and Tawhid Soderholm et al 15 found a decrease in cord arterial pH <7.1 in association with EA. One study 19 observed better cord pH in patients with EA.…”
Section: Discussionmentioning
confidence: 98%
“…This observation was noted in previous studies also. 7,15 Gestational diabetes is associated with significant neonatal morbidity. 16,65,66 There was no significant difference between the groups in terms of the number of gestational diabetic mothers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tawhid et al studied epidural analgesia in 1,449 parturient and found out that the rate of assisted vaginal delivery was significantly higher in the epidural analgesia group compared to the nonepidural analgesia group. 11 Agrawal et al concluded after the study on 120 parturient that there is no significant difference in neonatal outcome in parturient undergoing labor analgesia. 10 Vincent studied epidural analgesia in 1,500 parturient and reported good neonatal outcome and no significant adverse effects in neonates.…”
Section: Discussionmentioning
confidence: 99%